2012
DOI: 10.1016/j.acap.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Care and Attitudes Towards Shared Decision-making Among Low Socioeconomic Status Parents: Role of Health Literacy

Abstract: Objective Although low parent health literacy (HL) has been linked to poor child health outcomes, it is not known whether differences in perceptions related to access to care and provider–parent partnership in care are potential contributing factors. We sought to assess whether parent HL is associated with differences in perceived barriers to care and attitudes regarding participatory decision-making with the provider. Methods This was a cross-sectional analysis of data collected from parents presenting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 36 publications
2
78
0
1
Order By: Relevance
“…Low health literate parents depended on the diabetes educators to tell them what to do for diabetes care, focusing on the tasks or survival skills of diabetes care. This finding is consistent with previous findings that have found that low literate patients were more passive, relying on the health care provider to make decisions and to dictate care (Arthur, et al, 2009;Yin, et al, 2012).…”
Section: Health Literacy and Explanations Of Diabetes Caresupporting
confidence: 83%
See 1 more Smart Citation
“…Low health literate parents depended on the diabetes educators to tell them what to do for diabetes care, focusing on the tasks or survival skills of diabetes care. This finding is consistent with previous findings that have found that low literate patients were more passive, relying on the health care provider to make decisions and to dictate care (Arthur, et al, 2009;Yin, et al, 2012).…”
Section: Health Literacy and Explanations Of Diabetes Caresupporting
confidence: 83%
“…Low literate patients ask overall fewer questions during medical encounters compared to those with higher health literacy; in addition, the types of questions are qualitatively different with low literate patients requesting repetition or clarification of information rather than seeking new knowledge (Katz et al, 2007). Low health literate parents of children also reported a strong preference for relying on the doctor's knowledge and leaving decisions up to the doctor (Yin et al, 2012). One study, however, found that diabetes patients with low health literacy, reported greater self-efficacy with care when the provider used a collaborative style, although this finding was not observed in patients with higher health literacy (Ishikawa & Yano, 2011).…”
Section: Communication Processes: Eliciting Concerns and Decision-makingmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In the context of child growth and nutrition, low parent health literacy is associated with worse knowledge of breastfeeding, problems mixing infant formula correctly, difficulty understanding food labels and portion sizes, difficulty understanding standard growth charts, and higher BMI in children. 29,[34][35][36][37][38][39][40] Although clinical efforts to prevent childhood obesity have had a limited effect on school-aged children, 7,[41][42][43] few clinical trials have specifically addressed obesity prevention during the first years of life, and none has examined the effect of an intervention that integrates a literacy-sensitive approach. 6 In this report, we describe the Greenlight Intervention Study, a cluster randomized, multisite trial to assess the efficacy of a low literacy, primary care-based intervention to prevent early childhood obesity.…”
mentioning
confidence: 99%
“…Nearly 30% of US caregivers are estimated to have below basic or basic health literacy, 1,5 which has implications for child health. Parents with low health literacy may face more barriers to care 6 or lack communication and processing skills required to act appropriately on health care information for their children. 7 It may be difficult for these parents to understand immunization schedules, growth charts, or medical forms, or to follow written instructions and recommendations for their children's preventive health care.…”
mentioning
confidence: 99%